2020
DOI: 10.1002/ptr.6714
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of isorhamnetin on pulmonary arterial hypertension: in vivo and in vitro studies

Abstract: Pulmonary arterial hypertension (PAH) is a malignant disease with high mortality and closely involves the bone morphogenetic protein (BMP) pathway. Mutations in BMPR2 caused proliferation of pulmonary artery smooth muscle cells (PASMCs) leading to PAH. Isorhamnetin, one of the main naturally occurring flavonoids extracted from Hippophae rhamnoides L, shows antiinflammatory and anti-proliferative properties. Nevertheless, the effects of isorhamnetin on PAH remain unclear. This study aimed to investigate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Additionally, it may ameliorate acute kidney injury by inhibiting the NF-κB signaling pathway activation [ 31 ]. Additionally, isorhamnetin exhibits anti-thrombus [ 77 ], antihypertensive [ 78 ], anti-inflammatory [ 26 ], anti-osteoporosis [ 79 ], antiplatelet activity [ 80 ], hepatoprotective [ 81 ], and anti-hypoxia [ 82 ] effects. It has also been shown that isorhamnetin could boost innate immunity [ 83 ].…”
Section: General Overview Of Biological Activities Of Isorhamnetinmentioning
confidence: 99%
“…Additionally, it may ameliorate acute kidney injury by inhibiting the NF-κB signaling pathway activation [ 31 ]. Additionally, isorhamnetin exhibits anti-thrombus [ 77 ], antihypertensive [ 78 ], anti-inflammatory [ 26 ], anti-osteoporosis [ 79 ], antiplatelet activity [ 80 ], hepatoprotective [ 81 ], and anti-hypoxia [ 82 ] effects. It has also been shown that isorhamnetin could boost innate immunity [ 83 ].…”
Section: General Overview Of Biological Activities Of Isorhamnetinmentioning
confidence: 99%
“…The epidemiological studies indicated that the progress of PAH was prevented with various sourced flavonoids such as curcumin ( Rice et al, 2016 ), isoliquiritigenin ( Jin et al, 2019 ), isorhamnetin ( Chang et al, 2020 ), naringenin ( Ahmed et al, 2014 ), rulin ( Li et al, 2014 ), chrysin ( Li XW. et al, 2015 ), silibinin ( Zhang T. et al, 2020 ), formononetin ( Cai et al, 2019 ), apigenin ( He et al, 2020 ), and isoquercitrin ( Zhang Y. et al, 2017 ).…”
Section: Preclinical Studies Of Traditional Herbal Medicine For Pulmonary Arterial Hypertension Treatmentmentioning
confidence: 99%
“…et al, 2015 ), silibinin ( Zhang T. et al, 2020 ), formononetin ( Cai et al, 2019 ), apigenin ( He et al, 2020 ), and isoquercitrin ( Zhang Y. et al, 2017 ). When treated with the flavonoid of curcumin, isoliquiritigenin, isorhamnetin, or naringenin, hypoxia- or MCT-induced PAH rodents were significantly protected, with changes in inhibited inflammatory markers such as TNF-α, IL-1β, IL-6 ( Ahmed et al, 2014 ; Rice et al, 2016 ; Jin et al, 2019 ; Zhang T. et al, 2020 ; Chang et al, 2020 ), and BMP signaling ( Chang et al, 2020 ). Interestingly, the oxidative stress levels in PAH rodents, including decreased ROS and elevation of NOX4, were alleviated by treatment of naringenin, rulin, and chrysin ( Ahmed et al, 2014 ; Li et al, 2014 ; Li XW.…”
Section: Preclinical Studies Of Traditional Herbal Medicine For Pulmonary Arterial Hypertension Treatmentmentioning
confidence: 99%
“…Isorhamnetin (3,5,7-trihydroxy-2-[4-hydroxy-3-methoxyphenyl] chromen-4-one) is an important natural flavonoid extracted from the fruits of Hippophae rhamnoides L. and the leaves of Ginkgo biloba L. 6,7 To date, numerous investigations revealed that isorhamnetin has extensive pharmacological activities and biological effects, such as anti-inflammation, 8 antimicrobial, 9,10 cardiovascular and cerebrovascular protection, 11,12 antitumor, 13 and antioxidation. [14][15][16] For example, isorhamnetin could increase pathogen cell membrane permeability by generating oxidative species in a dose-dependent manner, 17 thus exhibiting antifungal activity on Aspergillus niger, Fusarium sporotrichum, and Candida albicans in vitro. 18 But whether isorhamnetin effects the growth of Aspergillus fumigatus, one of the most common fungal pathogens for FK, remains unknown.…”
mentioning
confidence: 99%
“…8 Isorhamnetin exerts protective effects on lipopolysaccharide (LPS)-induced acute lung injury in mice by inhibiting the expression of cyclooxygenase-2. 15 It also suppresses LPSmediated inflammatory response in BV2 microglia through inhibiting the nuclear factor (NF)-κB signaling pathway, downregulating Toll-like receptor 4 (TLR4) and eliminating reactive oxygen species accumulation. 21 In addition, the antituberculosis property of isorhamnetin has been reported in murine model via repressing the expression of proinflammatory mediators including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and IL-12.…”
mentioning
confidence: 99%